3D seismic reflection study for subsurface structural picture of Dujaila Oil Field, South of Iraq - A. Alridha, Nawal; A. Al-Khafajy, Hadeel A. (Iraqi Journal of Science, 2023)
This research represents a 3D seismic structural study for 602.62 Km2 of DujailaOil Field which is located 55 Km Northwest of Mysan province and 20 Km Southwestof Ali-AlSharki region within unstable Mesopotamian basin.Synthetic traces are prepared by using available data of two wells (Du-1, Du-2), inorder to define and pick the reflectors. Two reflectors are picked that represent the topand bottom of Mishrif Formation, in addition to five units within this Formation arepicked, they named Units 1, 2, 3, 4, and 5.Time maps for the top and bottom of Mishrif reflectors are drawn to get thestructural picture, these maps show general dip of layers toward NE, and thus, thereare two enclosure domes in the middle of Dujaila Oil Field where two wells (Du-1,Du-2) are found.